2012
DOI: 10.1080/17441692.2012.663399
|View full text |Cite
|
Sign up to set email alerts
|

Extending the income inequality hypothesis: Ecological results from the 2005 and 2009 Argentine National Risk Factor Surveys

Abstract: A consensus on income inequality as a social determinant of health is yet to be reached. In particular, we know little about the cross-sectional versus lagged effect of inequality and the robustness of the relationship to indicators that are sensitive to varying parts of the income spectrum. We test these issues with data from Argentina's 2005 and 2009 National Risk Factor Surveys. Inequality was operationalised at the provincial level with the Gini coefficient and the Generalised Entropy (GE) index. Populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 63 publications
0
5
0
1
Order By: Relevance
“…Thereby, it was suggested that under-reporting of poor health in deprived regions might be because people living in these areas are usually less aware of treatable conditions (Sen, 2002). If true, this will ultimately lead to an underestimate of the social gradient in health (De Maio et al, 2012) and needs to be taken into account when interpreting the findings of the present study. Additionally, the survey only covered urban populations (close to 85% of the total population of the country; Dachs et al, 2002), avoiding comparisons between urban and rural adults.…”
Section: Discussionmentioning
confidence: 81%
“…Thereby, it was suggested that under-reporting of poor health in deprived regions might be because people living in these areas are usually less aware of treatable conditions (Sen, 2002). If true, this will ultimately lead to an underestimate of the social gradient in health (De Maio et al, 2012) and needs to be taken into account when interpreting the findings of the present study. Additionally, the survey only covered urban populations (close to 85% of the total population of the country; Dachs et al, 2002), avoiding comparisons between urban and rural adults.…”
Section: Discussionmentioning
confidence: 81%
“…However, this would not have affected the associations between Gini coefficient and mortality reported here. Using contemporaneous Gini coefficients and mortality may not have captured any delayed effects of inequality on health, which some have suggested in previous studies [31]. This ecological analysis describes associations at the population level, which may not be replicated at the individual level.…”
Section: Discussionmentioning
confidence: 97%
“…The Gini coefficient is derived from the Lorenz curve of the plot of cumulative percentage of the population by socio-economic status and cumulative percentage of total income. The Gini coefficient is calculated as the ratio of the area between the Lorenz curve and the 45° line, to the whole area below the 45° line; a Gini coefficient of 0 reflects a perfectly equal society, and a Gini coefficient of 1 represents a perfectly unequal society [ 15 , 16 ]. The Brown formula is used for this purpose [ 17 ].…”
Section: Methodsmentioning
confidence: 99%